2019
DOI: 10.1371/journal.pone.0222848
|View full text |Cite
|
Sign up to set email alerts
|

High levels of fasting glucose and glycosylated hemoglobin values are associated with hyperfiltration in a Spanish prediabetes cohort. The PREDAPS Study

Abstract: AimThis study aimed to investigate whether different levels of fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) in prediabetes are associated with hyperfiltration.MethodsA prospective cohort of 2,022 individuals aged 30–74 years took part in the PREDAPS Study. One cohort of 1,184 participants with prediabetes and another cohort of 838 participants with normal FPG and normal HbA1c were followed for 5 years. Hyperfiltration was defined as an estimated glomerular filtration rate (eGFR) above the age- and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Due to hyperglycemia-related hyperfiltration, the measured GFR decreased from 149 to 129 ml/min per 1.73 m 2 (16% reduction) after HbA 1c dropped from 10% to 7% and increased significantly toward the baseline values along with HbA 1c control deterioration in patients with T1D ( 20 ). Additionally, HbA 1c was positively associated with eGFR, whether independently or together with fasting plasma glucose (FPG), in participants with prediabetes and was associated with significantly increased odds ratios (ORs) of hyperfiltration ( 21 , 22 ). It was reported that every 1% increase in HbA 1c levels and a 2.0 mmol/L increase in 2-h post-load glucose (2hPG) were associated with a 17% and 61.4% higher risk of hyperfiltration, respectively ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to hyperglycemia-related hyperfiltration, the measured GFR decreased from 149 to 129 ml/min per 1.73 m 2 (16% reduction) after HbA 1c dropped from 10% to 7% and increased significantly toward the baseline values along with HbA 1c control deterioration in patients with T1D ( 20 ). Additionally, HbA 1c was positively associated with eGFR, whether independently or together with fasting plasma glucose (FPG), in participants with prediabetes and was associated with significantly increased odds ratios (ORs) of hyperfiltration ( 21 , 22 ). It was reported that every 1% increase in HbA 1c levels and a 2.0 mmol/L increase in 2-h post-load glucose (2hPG) were associated with a 17% and 61.4% higher risk of hyperfiltration, respectively ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would explain our findings that when eGFR is less than 130 ml/min/1.73m 2 , declining eGFR is associated with an increased risk of developing pre-diabetes in the future. However, it has also been shown that pre-diabetes is strongly related to glomerular hyperfiltration ( 17 , 47 49 ). Glomerular hyperfiltration has been associated with the early stages of nephropathy that evolved into CKD ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…63 Similarly, prediabetes has been associated with dysfunction of the kidney. 30,62,[64][65][66][67][68][69][70][71][72] Evidence of neuropathy or microvascular dysfunction has been found in people with vs without prediabetes in skin, 56 the heart, 73,74 and in sensory nerves. 75 Other studies showed trends to adverse changes in nerve function, rather than overt neuropathy, in people with prediabetes.…”
Section: Clinical Relevance Of the Diabetes Continuum Glycaemic Controlmentioning
confidence: 99%